Pemodelan Pencegahan Penularan Scabies - Utami, Nita (UIN Imam Bonjol Padang, 2021)
Health is the most important thing for every individual, because if illness has approached the individual, whatever the disease is, it becomes a fear that cannot be defeated by anything except by the power of God. The skin is a part of the human body that is quite sensitive to various diseases. Skin disease can be caused by many factors. Scabies is a skin disease caused by Sarcoptes scabei variant hominis (a type of tick, mite), characterized by complaints of itching, especially at night and transmitted through direct or indirect contact through former bedding or bedding. clothes. To overcome the transmission of scabies, the purpose of this study is how to mathematically model the prevention of scabies transmission?. The method used is Stability Theory.